Perpustakaan dan Penerjemahan Buku-Buku Teks Islam - Salam, Yufridal Nur (Pustakaloka, 2010)
Islam has a distinctive nature in the development of its dogma, such as by libraries and translation activities. these activities grow in accordance with the times so that it cannot be denied that one of the means to convey the religious message is the development of opinion. Whoever evolves opinion rapidly becomes the one who rules the world. Library is a means of developing such an opinion and the translation process is te gateway to the opening of opinions to anyone and anywhere.